Characterization of the complete chloroplast genome of a subalpine deciduous shrub Lonicera angustifolia var. myrtillus (Caprifoliaceae). Issue 7 (3rd July 2021) - Wu, Yuan-Mi; Ma, Di; Zhu, Yi-Xuan; Liu, Bing; Mu, Xian-Yun
Abstract: The genus Lonicera (Caprifoliaceae) is of great economical significance. It has been taxonomically studied frequently in history, while phylogenetic relationships intra the genus are still obscure. Here, we reported the first species complete chloroplast genome sequence in the section Isoxylosteum, Lonicera angustifolia var. myrtillus . It is 156, 222 bp in length, comprising a large single-copy (LSC) region of 89, 838 bp, a small single-copy (SSC) region of 19, 211 bp, and a pair of inverted repeats (IRs) of 23, 509 bp. In L. angustifolia var. myrtillus chloroplast genome, a total of 114 functional genes were identified, with an overall GC content of 38.4%. The phylogenetic relationships of Lonicera based on maximum-likelihood (ML) showed that L. angustifolia var. myrtillus is most closely related to L. nervosa in section Isika . Our study contributes to the molecular phylogenetic studies of Lonicera and Caprifoliaceae.